Legal Protection Of Children With Special Needs In The Era Covid-19 According To Islamic law Perspective - Mhd Yadi Harahap; Hafsah; Mashuri Siregar Hall; M. Fajri Syahroni Siregar (Asian Journal of Law and Humanity, 2022)
This paper analyzes the legal protection of children with special needs during the COVID-19 pandemic. This legal sociology research uses a qualitative approach. The research location is in Medan, North Sumatra province. The results show that the legal protection of children with special needs in Medan City, North Sumatra province related to education, rehabilitation, and social assistance is still not fulfilled even though there are regional regulations in the province of North Sumatra. This is due to inadequate facilities and infrastructure that hinder the fulfillment of these rights. This is contrary to Islamic law, where children's rights must be guaranteed, protected, and fulfilled by maqashid al-syari'ah, namely the maintenance of offspring. It also contradicts Article 5 paragraph (1) of Law Number 8 of 2016 concerning Persons with Disabilities, that persons with disabilities have the same rights in life and livelihood.